Biological Effects of HDAC Inhibitors Vary with Zinc Binding Group: Differential Effects on Zinc Bioavailability, ROS Production, and R175H p53 Mutant Protein Reactivation - Brianna M. Flores; Chandana K. Uppalapati; Agnes S. Pascual; Alan Vong; Margaux A. Baatz; Alisha M. Harrison; Kathryn J. Leyva; Elizabeth E. Hull (Biomolecules, 2023)
The coordination of zinc by histone deacetylase inhibitors (HDACi), altering the bioavailability of zinc to histone deacetylases (HDACs), is key to HDAC enzyme inhibition. However, the ability of zinc binding groups (ZBGs) to alter intracellular free Zn+2 levels, which may have far-reaching effects, has not been explored. Using two HDACis with different ZBGs, we documented shifts in intracellular free Zn+2 concentrations that correlate with subsequent ROS production. Next, we assayed refolding and reactivation of the R175H mutant p53 protein in vitro to provide greater biological context as the activity of this mutant depends on cellular zinc concentration. The data presented demonstrates the differential activity of HDACi in promoting R175H response element (RE) binding. After cells are treated with HDACi, there are differences in R175H mutant p53 refolding and reactivation, which may be related to treatments. Collectively, we show that HDACis with distinct ZBGs differentially impact the intracellular free Zn+2 concentration, ROS levels, and activity of R175H; therefore, HDACis may have significant activity independent of their ability to alter acetylation levels. Our results suggest a framework for reevaluating the role of zinc in the variable or off-target effects of HDACi, suggesting that the ZBGs of HDAC inhibitors may provide bioavailable zinc without the toxicity associated with zinc metallochaperones such as ZMC1.